1988
DOI: 10.2170/jjphysiol.38.427
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between calcium-mediated and cyclic AMP-mediated activation of chloride secretion in isolated guinea pig distal colon.

Abstract: Synergistic effects of Cat +-mediated secretagogues and cyclic AMP-mediated secretagogues on Cl -secretion by guinea pig distal colon were studied in vitro using Ussing chambers. Short-circuit current (ISO) and bidirectional fluxes of Z2Na + and 3601-were measured. Bethanechol (10-4 M, a Cat+-mediated secretagogue) caused an increase in ISO, which was enhanced 4-20 fold when the tissue was pretreated with prostaglandin E2 (10-'-10-6 M), vasoactive intestinal polypeptide (5 x 10-9-10_8 M) (cyclic AMP-mediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…The observation that NPPB and glibenclamide had non-additive effects on Isc and that the reversal potentials for NPPB-and glibenclamide-sensitive currents were nearly identical indicates that these compounds block the same population of basally active Cl¦ channels. Previous studies using porcine and guinea-pig colon as well as T84 cells showed that PGEµ stimulates Cl¦ secretion (Weymer, Huott, Lui, McRoberts & Dharmsathaphorn, 1985;Yajima, Suzuki & Suzuki, 1988;Traynor et al 1993). Treatment of porcine endometrial epithelial cell monolayers with PGEµ produces a concentration-dependent increase in Isc which is blocked by pretreatment with NPPB or glibenclamide and by Cl¦ replacement.…”
Section: Discussionmentioning
confidence: 93%
“…The observation that NPPB and glibenclamide had non-additive effects on Isc and that the reversal potentials for NPPB-and glibenclamide-sensitive currents were nearly identical indicates that these compounds block the same population of basally active Cl¦ channels. Previous studies using porcine and guinea-pig colon as well as T84 cells showed that PGEµ stimulates Cl¦ secretion (Weymer, Huott, Lui, McRoberts & Dharmsathaphorn, 1985;Yajima, Suzuki & Suzuki, 1988;Traynor et al 1993). Treatment of porcine endometrial epithelial cell monolayers with PGEµ produces a concentration-dependent increase in Isc which is blocked by pretreatment with NPPB or glibenclamide and by Cl¦ replacement.…”
Section: Discussionmentioning
confidence: 93%
“…Addition of PGE 2 (3 M) stimulates sustained Cl Ϫ secretion together with K ϩ secretion, a flushing type response. The cholinergic agonist carbachol (CCh; 10 M) added cumulatively with PGE 2 (3 M) produces a synergistic flushing secretion (8,18,76). However, CCh addition from the basal state stimulates a negative I sc consistent with modulatory type K ϩ secretion (41).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the more familiar flushing mode exhibits both sustained Cl Ϫ and K ϩ secretion stimulated most commonly via prostanoid pathways (28,49,55). The highest rates of secretion are seen with the combined activation of prostanoid and cholinergic pathways, suggesting a synergistic interaction (8,18,76). This apparent regulatory synergism may result from the actions of cytosolic cAMP and Ca 2ϩ to stimulate the K ϩ channels necessary for secretion (23,47).…”
mentioning
confidence: 99%
“…Three modes of electrogenic ion secretion (11,25,33,49,52) were stimulated by secretagogs to examine the action of the neuroendocrinepeptide PYY, epinephrine for modulatory mode, PGE 2 for flushing mode, and PGE 2 ϩ carbachol (CCh) for synergistic mode. Adding PYY to the serosal bathing solution during the basal quiescent state reduced the negative I sc toward zero and decreased G t (Fig.…”
Section: Suppression Of CLmentioning
confidence: 99%